Seroprevalence of Toxoplasma gondii in wild boar and deer in Brandenburg, Germany. (14th April 2020) - Bier, Nadja Seyhan; Stollberg, Kaya; Mayer‐Scholl, Anne; Johne, Annette; Nöckler, Karsten; Richter, Martin
Abstract: Consumption of game in Germany has increased during the past 10 years. Wild boar ( Sus scrofa ), roe deer ( Capreolus capreolus ) and red deer ( Cervus elaphus ) are the most frequently hunted and consumed game animals in Germany, yet information on the occurrence of zoonotic pathogens in these animal species is scarce. To better estimate the public health risk emanating from handling and consumption of game, this study investigated seroprevalences of Toxoplasma gondii in game hunted in the German federal state of Brandenburg during two hunting seasons from 2017 to 2019. Toxoplasma gondii ‐specific antibodies were detected in 24.4% (44/180, 95% CI: 18.4%–31.4%) of wild boar, 12.8% (16/125, 95% CI: 7.5%–20%) of roe deer and 6.4% (3/47, 95% CI: 1.3%–17.5%) of red deer using a commercial ELISA kit. Seroprevalences were similar in the two hunting seasons. Correlation between sex and seropositivity could not be observed. A rise in seroprevalence was seen with increasing age in all studied game species. Observed seroprevalences suggest that T. gondii is endemic in the sylvatic environment in the German federal state of Brandenburg and imply that game could represent a relevant source for human T. gondii infection.